How long does it take you to pay? A duration study of canadian retail transaction payment times - Geneviève Vallée (Bank of Canada, 2018)
Using an exclusive data set of payment times for retail transactions made in Canada, I show that cash is the most time-efficient method of payment (MOP) when compared with payments by debit and credit cards. I model payment efficiency using Cox proportional hazard models, accounting for consumer choice of MOP. I propose two instruments to identify and estimate the causal relationship between MOP and payment time: (1) the value of the transaction, and (2) the duration of the payment preceding the one under observation. Discounting consumer selection underestimates the efficiency of cash relative to cards. Overall, the efficiency of MOPs is an important component of the private and social costs of making and accepting payments. The efficiency of cash helps explain its continued use in Canada, which is motivated by its low cost in terms of payment time for consumers and merchants.
Keywords: C25; C36; C41; D23; E41; E42; 330; Bank notes; Econometric and statistical methods; Payment clearing and settlement systems